2017
DOI: 10.1021/acs.energyfuels.7b00208
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Fe–Ni–Al Oxygen Carrier Derived from Hydrotalcite-like Precursors for the Chemical Looping Gasification of Biomass Char

Abstract: Chemical looping gasification (CLG) of biomass uses the lattice oxygen of oxygen carriers to convert biomass into syngas with a low tar content, high heating value, and low price. It is of key importance to exploit well-dispersed and thermally stable oxygen carriers for the CLG process. In the current work, a series of oxygen carriers with varied Fe and Ni molar ratios were synthesized from hydrotalcite compound precursors (HTlcs), which made the metallic elements mix at the molecular level. Consequently, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Mixed oxides, which integrate the merits of different components and weaken the disadvantages of single phases, may attain a synergetic effect in reaction and provide better performance in comparison to that of individual metal oxides. With this regard, different mixed oxides, such as Cu–Fe, Ni–Fe, Co–Fe, Mn–Fe, , and Ca–Fe, have been synthesized and tested as oxygen carriers in chemical looping processes.…”
Section: Development Of Oxygen Carriers For Clc Of Coalmentioning
confidence: 99%
“…Mixed oxides, which integrate the merits of different components and weaken the disadvantages of single phases, may attain a synergetic effect in reaction and provide better performance in comparison to that of individual metal oxides. With this regard, different mixed oxides, such as Cu–Fe, Ni–Fe, Co–Fe, Mn–Fe, , and Ca–Fe, have been synthesized and tested as oxygen carriers in chemical looping processes.…”
Section: Development Of Oxygen Carriers For Clc Of Coalmentioning
confidence: 99%
“…Due to its low price and non-toxicity, Fe is advantageous from an economic and environmental point of view compared to Ni. Aiming to combine the complementary advantages of these two constituent metals, many efforts have been made to develop bimetallic Fe-Ni oxygen carriers via two different main strategies, physical [108,133] and chemical [23,108,109,110,111,112] mixing. Johansson et al [133] reported that the addition of only 3 wt % NiO in the bed of a Fe-based oxygen carrier was sufficient to reach a very high CH 4 conversion in CLC process.…”
Section: Improvements To Oxygen Carriersmentioning
confidence: 99%
“…[ 69–71 ] In specific cases, biochars have been used as the reducing agents in TGA. [ 72 ] As shown in Figure 5, OTCs measured by TGA vary from 1 wt% (e.g., in the case of iron oxide‐based LD slag) to 12 wt% (e.g., in the case of 60 wt% NiO supported on MgAl 2 O 4 ). Under chemical looping operations, other rate limiting factors such as intraparticle mass transfer resistance and product layer diffusional resistance could further reduce the practically available OTC, [ 22,73–75 ] unless the issues above can be adequately addressed through improved OC designs.…”
Section: Overview Of Oxygen Carriersmentioning
confidence: 99%
“…studied Fe‐Al‐Ni OCs using a combined TGA‐XRD approach, which directly established the correlation between the DTG peaks during TPR and the specific phase transformations. [ 72 ] Their results shows that the two DTG peaks could be assigned to the reduction of Fe 0.99 Ni 0.6 Al 1.1 O 4 to Fe 1– x O and the subsequent reduction to metallic Fe.…”
Section: Overview Of Oxygen Carriersmentioning
confidence: 99%